PERBANYAKAN ANGGREK Grammatophyllum scriptum (Lindl.) BL. MELALUI INDUKSI TUNAS SECARA IN VITRO DENGAN PENAMBAHAN BAP dan NAA - Angriawan Markal; Mayta Novaliza Isda; Siti Fatonah (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Grammatophyllum scriptum (Lindl.) BL. is one of orchid species that pottentially to be extinct in the nature. In order to maintain the existence of this orchid, a propagation is needed, such as using in vitro culture techniques. This study aimed to determine the influence and the best concentration of BAP in single treatment, as well as the combination with NAA in inducing in vitro bud explant of G. scriptum. This study used a completely randomized design (CRD) with various concentrations of BAP only or in combination with NAA. The results of this study showed that the treatment of 1 mg /l BAP gave the best results with 100% orchid bud formation, 13.67 of formation of buds after planting day, with number of bud and and leave were 3,33 and 5,33, respectively. While the best combination of BAP and NAA for shoot growth was 1 mg / l BAP + 0.5 mg / l NAA, with the formation of shoot was 13,33 after planting day, 2.33 buds, and 5.67 leaves.